Role of Brain Angiotensin-II in Development of Experimental Diabetic Nephropathy in Wistar Rats - Anubhav Kumar Singh; Niraj Kumar Singh; Ahsas Goyal; Bhupesh Chander Semwal; Harlokesh Narayan Yadav (Universidade de São Paulo, 2023)
Abstract The renin-angiotensin-aldosterone system (RAAS) plays a key role in diabetic nephropathy (DN). Angiotensin-II secreted during the RAAS pathway increases nephropathy. It stimulates oxidative stress which can quench nitric oxide. Reduced nitric oxide level aggravates Ang-II-induced vasoconstriction. Ang-II has also emerged as a central mediator of the glomerular hemodynamic changes that are associated with renal injury. Deletion of ACE2 is also noted due to increased Ang-II level which leads to the development of DN. We hypothesize that nephropathy caused by Ang-II in the periphery may be controlled by brain RAAS. ACE inhibitors and ARBs may show the renoprotective effect when administered through ICV without crossing the blood-brain barrier. DN was observed after 8 weeks of diabetes induction through alloxan. Administration of captopril and valsartan once and in combined therapy for 2 weeks, significantly reduced urine output, blood urea nitrogen, total protein in the urine, serum cholesterol, serum creatinine, serum triglycerides, and kidney/body weight ratio as compared to diabetic control rats. Further, combination therapy significantly increased the body weight and serum nitrate level as compared to diabetic control animals. However, increased ACE2 levels in the brain may reduce the sympathetic outflow and might have decreased the peripheral activity of Ang-II which shows beneficial effects in DN.